The Influence of Student Participation in Career Planning Programs at Higher Education Institutions on Students' Work Readiness with Motivation as a Moderating Variable - Lintang Viennetta Naura Berbyani; Nur Achmad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: The purpose of this study is to examine the influence of student participation in university career planning programs on work readiness, while also analyzing the role of motivation as a moderating variable in this relationship.Methodology: This research employs a quantitative approach involving 190 active university students who have participated in career planning programs. Data were collected through a structured questionnaire and analyzed using the SEM-PLS technique with SmartPLS 4 software to assess the direct and moderating effects among variables. Results: The findings indicate that student participation in career planning programs has a positive and significant effect on work readiness. Motivation also demonstrates a direct and significant influence on work readiness; however, it does not moderate the relationship between student participation and work readiness.Applications/Originality/Value: This study provides empirical evidence on how university career planning program participation contributes to improving students' work readiness. The results offer valuable insights for higher education institutions in designing, enhancing, and implementing more effective career development initiatives. Additionally, the study contributes originality by integrating motivation as a potential moderating variable within the context of career planning and work readiness.